Castellinaria, and Other Sicilian Diversions - Jones, Henry Festing, 1851-1928 (Salt Lake City, UT : Project Gutenberg, 2008)
"Castellinaria and Other Sicilian Diversions" by Henry Festing Jones is a collection of personal narratives and observations reflecting life in Sicily, written in the early 20th century. The book seems to explore the culture, traditions, and characters of Sicilian society through the author's experiences and interactions, primarily involving the Pampalone family, particularly Peppino, Brancaccia, and their son Enrico (referred to as Ricuzzu). The opening of the work introduces readers to the enchantment of Sicilian life through the birth and christening of Enrico Pampalone, characterized by warmth, family connections, and a blend of joy and sorrow. As the author receives news about the child's birth and partakes in the family's life, we gain insight into their dynamics and the traditions surrounding godparentage in Sicilian culture. Through rich descriptions of the surroundings and lively exchanges, the reader gets a taste of the local customs, the beauty of the Sicilian landscape, and the emotional undercurrents of the Pampalone family, setting the stage for further explorations of the island$1 (Bs cultural richness. (This is an automatically generated summary.)s
Release date is 2008-04-15
This ebook was transcribed by Les Bowler
Keywords: Sicily (Italy) -- Description and travel